Shift work sleep disorder and job stress in shift nurses: implications for preventive interventions - d’Ettorre, Gabriele (Med Lav, 2020)
BACKGROUND: A growing literature has revealed a relationship between shift-work, including night-shift, and the disturbance of sleep-wake cycle, leading to insomnia and/or increased daytime sleepiness in shift nurses; recent findings showed an association between shift work sleep disorders and distress, work accidents, decreased job performance and, consequently, lower quality of health service provision and lower standards of care. OBJECTIVES: To analyze across the gender how shift nurses experience shift work sleep disorders and job stress. METHODS: A cross-sectional study was performed following the STROBE Statement. The Italian version of the Job Content Questionnaire, the Bergen Insomnia Scale and the Epworth Sleepiness Scale were administered to the registered nurses employed in three Departments of General Practice and Elderly Care Medicine. RESULTS: No significant association was found between high job strain and insomnia and daytime sleepiness. Significantly more women than men experienced high job strain, insomnia and daytime sleepiness; among women the level of social support was significantly and negatively associated with insomnia and daytime sleepiness. CONCLUSIONS: The findings of this study suggest that interventions aimed to prevent shift work sleep disorder and job stress in shift-nurses should incorporate the assessment of social support across the gender. Moreover, longitudinal studies are required to evaluate the effectiveness of interventions targeted on social support to minimize the occurrence of insomnia and daytime sleepiness in shift nurses.